2004
DOI: 10.1108/09604520410528662
|View full text |Cite
|
Sign up to set email alerts
|

Customer involvement in new service development: a conversational approach

Abstract: The expression "customer involvement" is finding increasing popularity with popular as well as academic marketing texts. Within the evolving research, customer involvement is cast in an information-processing mould that tends to reduce it to the mere transfer of information from where it exists (customers) to where it is dearly needed (the firm). Customers' active participation is accounted for in economic psychological (contract) terms. Drawing on case study material gleaned from an organisation that adopted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
92
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(93 citation statements)
references
References 27 publications
1
92
0
Order By: Relevance
“…Involving the customer provides a correct innovation direction and enables the firm to reduce the investment costs, time, and diversity of uncertainty that may occur in the innovation process [26,27].…”
Section: Technology-explorationmentioning
confidence: 99%
“…Involving the customer provides a correct innovation direction and enables the firm to reduce the investment costs, time, and diversity of uncertainty that may occur in the innovation process [26,27].…”
Section: Technology-explorationmentioning
confidence: 99%
“…Strategic minded firms harness the creativity of their customers and blend it with their own dynamic capabilities to co-create products, solutions, communications, and experiences. Consequently, to reduce uncertainties of new product development process (NPDP), consumers are actively involved in the entire process (Kaulio, 1998;Lundkvist and Yakhelf, 2004;Hanna et al, 1995;Ciccantelli and Magidson, 1993) though different firms observe this collaboration at different stages of NPDP (Lagrosen, 2005). …”
Section: Critical Analysis Of the Changes In Consumers' Participatorymentioning
confidence: 99%
“…However, the specific actions and behaviors that make up co-creation have not yet been fully addressed (Witell et al, 2011). Gruner and Homburg (2000) and Lundkvist and Yakhlef (2004) argued that the process of communication and socially rich interactions with customers is one of the determinants for product success. Furthermore, Payne et al (2006) reported that communication is an important element in a company's ability to manage value co-creation.…”
Section: Introductionmentioning
confidence: 99%